Spectroscopic Observation of Calcium‐Induced Reorientation of Cellobiose Dehydrogenase Immobilized on Electrodes and its Effect on Electrocatalytic Activity. Issue 9 (23rd April 2015) - Kielb, Patrycja; Sezer, Murat; Katz, Sagie; Lopez, Francesca; Schulz, Christopher; Gorton, Lo; Ludwig, Roland; Wollenberger, Ulla; Zebger, Ingo; Weidinger, Inez M.
Abstract Cellobiose dehydrogenase catalyzes the oxidation of various carbohydrates and is considered as a possible anode catalyst in biofuel cells. It has been shown that the catalytic performance of this enzyme immobilized on electrodes can be increased by presence of calcium ions. To get insight into the Ca2+‐induced changes in the immobilized enzyme we employ surface‐enhanced vibrational (SERR and SEIRA) spectroscopy together with electrochemistry. Upon addition of Ca2+ ions electrochemical measurements show a shift of the catalytic turnover signal to more negative potentials while SERR measurements reveal an offset between the potential of heme reduction and catalytic current. Comparing SERR and SEIRA data we propose that binding of Ca2+ to the heme induces protein reorientation in a way that the electron transfer pathway of the catalytic FAD center to the electrode can bypass the heme cofactor, resulting in catalytic activity at more negative potentials.